Answer:
f(h(-1)) = -1
Step-by-step explanation:
f(x) = (x-4)/3
h(x) = 3x + 4
f(h(-1)) = ?
So first off we need to solve for h(-1):
h(x) = 3x + 4
h(-1) = 3(-1) + 4
h(-1) = 1
Next, we plug this value into the f(x) equation:
f(x) = (x-4)/3
f(1) = (1-4)/3
f(1) = -1
f(h(-1)) may look confusing but it is just f(x) with x being the resulting value for h(-1)
Thus we can say that f(h(-1)) is equal to -1
3. .5*60 because .5 represents the 5% and "of" stands for multiplication
Step-by-step explanation:
So you should use headphones while doing writing work and if digital work then take very short brakes during study and concentrate fully.
here's the right answer!
A) 76 + 80 + 78 + x = 82 times 4
234 + x = 328
x = 94
B) Mei needs a score of at least 94 on the next exam.
hope you have a good day